Rhodium‐Catalyzed Enantioselective Formal [4+1] Cycloaddition of Diazooxindoles and the Danishefsky Diene. Issue 2 (19th January 2018) - Cao, Fei; Hu, Fang; Xie, Qi‐Mei; Luo, Gao‐Ya; Chu, Wen‐Dao; He, Long; Liu, Quan‐Zhong
Abstract: Optically enriched cyclopentenones are synthetically versatile molecules, and their rapid and efficient straightforward assembly from simple starting materials is highly desired. Herein, we report a rhodium‐catalyzed enantioselective formal [4+1] cycloaddition of diazooxindoles and the Danishefsky diene. The formation of cyclopentenones proceeds via ring expansion of the vinylcyclopropanes formed in situ via cyclopropanation. The optically and highly structurally enriched indoline spirocyclopentenone bearing an all‐carbon stereocenter was formed in a one‐pot, two‐step manner in good to excellent yields and enantioselectivities (up to 90 % ee ). Abstract : From 3 to 5 : A rhodium‐catalyzed enantioselective formal [4+1] cycloaddition of diazooxindoles and the Danishefsky diene is described. A series of synthetically interesting indoline spirocyclopentenones bearing an all‐carbon stereocenter were formed in a one‐pot, two‐step manner in good to excellent yields and enantioselectivities (up to 90 % ee ). The formation of cyclopentenones proceeds via ring expansion of the vinylcyclopropanes formed in situ via cyclopropanation.